STUDI FLUKTUASI SUHU HARIAN DI SEKARAN, SEMARANG BERBASIS ANALISIS DATA PYTHON - Ariana Indah Safitri (Kohesi: Jurnal Sains dan Teknologi, 2025)
This study analyzes daily temperature fluctuations in the Sekaran area of Semarang using a computational approach based on Python. Daily temperature and humidity data were obtained from the BMKG Ahmad Yani Semarang Meteorological Station and processed through data cleaning, missing value interpolation, and descriptive statistical analysis. The K-Means clustering algorithm was applied to group temperature and humidity patterns, while Monte Carlo simulation and LSTM (Long Short-Term Memory) simulation were used to identify long-term patterns in the daily time series. The analysis results show that daily temperatures in Sekaran fluctuate between 22°C and 32°C with a 24-hour periodic pattern and an amplitude of approximately 10.55°C. The urban heat island phenomenon and the city's surface thermal characteristics influence these patterns, with the highest temperatures occurring during the day and the lowest temperatures at early morning. Visualizations developed with Python facilitate monitoring and interpretation of daily temperature data. These findings are expected to support climate change adaptation planning, disaster risk mitigation, and the development of thermal comfort strategies in tropical urban areas like Sekaran. Penelitian ini menganalisis fluktuasi suhu harian di daerah Sekaran, Semarang menggunakan pendekatan komputasional berbasis Python. Data suhu dan kelembapan harian diperoleh dari BMKG Stasiun Meteorologi Ahmad Yani Semarang dan diproses melalui tahapan pembersihan data, interpolasi nilai hilang, serta analisis statistik deskriptif. Algoritma pengelompokan K-Means digunakan untuk mengelompokkan pola suhu dan kelembaban dan menggunakan simulasi Monte Carlo dan simulasi SSTM (memori jangka pendek jangka panjang) untuk mengidentifikasi pola jangka panjang dalam seri waktu sehari-hari.. Hasil analisis menunjukkan suhu harian di Sekaran berfluktuasi antara 22°C hingga 32°C dengan pola periodik 24 jam dan amplitudo sekitar 10,55°C. Fenomena urban heat island dan karakteristik termal permukaan kota memengaruhi pola tersebut, dengan suhu tertinggi terjadi pada siang hari dan suhu terendah pada dini hari. Visualisasi yang dikembangkan dengan Python memudahkan pemantauan dan interpretasi data suhu harian, dengan temuan ini diharapkan dapat mendukung perencanaan adaptasi perubahan iklim, mitigasi risiko bencana, dan pengembangan strategi kenyamanan termal di wilayah perkotaan tropis seperti Sekaran.